Preparation method of epoxy resin composite material with low temperature medium leakage resistance
By coating the organic polymer on the surface of MXene, PU-MXene is prepared and composited with epoxy resin, the microcrack problem caused by temperature stress in traditional composite materials in low temperature environments is solved, and the leakage resistance and mechanical properties of low temperature media are significantly improved. It is suitable for carrier rocket propellant storage tanks.
Patent Information
- Application Number
- CN202410059247.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-15
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-01-15
AI Technical Summary
Traditional carbon fiber reinforced epoxy resin-based composite materials are prone to microcracks caused by temperature stress in low temperature environments, which in turn leads to liquid propellant leakage, limiting their application in carrier rocket propellant storage tank structural materials.
By coating the organic polymer on the MXene surface, PU-MXene is prepared and composited with epoxy resin, the dispersion of MXene in epoxy resin is significantly improved, and the anti-low-temperature medium leakage and mechanical properties of the composite material are improved.
The PU-MXene epoxy resin is significantly improved to resist leakage and mechanical properties of low-temperature medium, and the prepared PU-MXene epoxy resin/carbon fiber composite material is suitable for the manufacture of composite low-temperature propellant storage tanks for launch vehicles.
Smart Images

Figure CN117887211B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an epoxy resin composite material with low-temperature medium leakage resistance, and belongs to the technical field of polymer materials. Background Art
[0002] Traditional launch vehicle cryogenic propellant tanks are made of metal materials, which are heavy, complex in manufacturing process and expensive. With the increasing requirements for lightweighting of space vehicles, traditional aluminum alloy materials as structural materials for launch vehicle propellant tanks have reached their upper limit in terms of lightweighting, so people have turned their research direction to carbon fiber reinforced epoxy resin-based composite materials. Compared with metal tanks, carbon fiber reinforced epoxy resin-based composite materials can reduce the weight of the tank structure by 25% to 35%, greatly improving the rocket's carrying efficiency.
[0003] However, when using carbon fiber reinforced epoxy resin-based composite materials to prepare low-temperature propellant tanks for launch vehicles, the temperature stress of the material needs to be considered. That is, the propellants of launch vehicles are mainly liquid oxygen (-183℃) and liquid hydrogen (-252℃). In a low-temperature environment, the epoxy resin molecular chain shrinks significantly, which causes a large temperature stress on the resin matrix / fiber interface of the carbon fiber reinforced epoxy resin-based composite material, which makes it easy for microcracks to initiate inside the composite material. The microcracks further expand into through cracks, eventually leading to liquid propellant leakage and safety accidents. Due to the existence of the above problems, the application of carbon fiber reinforced resin-based composite materials in the structural materials of launch vehicle propellant tanks is greatly limited.
[0004] In order to improve the low-temperature medium leakage resistance of carbon fiber reinforced resin-based composite materials, the prior art usually introduces flexible polymers into the epoxy resin molecular structure to improve the toughness of the resin matrix, that is, by improving its mechanical properties at low temperatures to improve the low-temperature medium leakage resistance of carbon fiber reinforced epoxy resin-based composite materials. However, this method cannot fundamentally solve the problem of microcracks caused by temperature stress, because the introduction of flexible molecular chains will increase the thermal expansion coefficient of the epoxy resin matrix. When the ambient temperature of the carbon fiber reinforced resin-based composite material drops from room temperature to ultra-low temperature, the thermal expansion coefficient of the resin matrix is large, which causes the temperature stress of the resin / fiber interface to increase sharply, which in turn easily leads to the initiation of microcracks at the resin / fiber interface, and may eventually reduce the low-temperature medium leakage resistance of the carbon fiber resin-based composite material.
[0005] In addition, the prior art, such as CN103435975B, mentions a method for improving the anti-leakage performance of composite materials by adding magnetic graphene, and the magnetic graphene can be distributed in an epoxy resin matrix in a directional and orderly manner under the action of a magnetic field. However, this technical method is difficult to operate. For large-sized composite tanks, it is difficult to apply a magnetic field in a large space; in addition, the graphene surface is only loaded with magnetic particles, and the dispersion of graphene in epoxy resin cannot be guaranteed, which is prone to agglomeration, resulting in a decrease in the mechanical properties of the composite material; at the same time, there are no active functional groups on the graphene surface, resulting in no covalent bonding between graphene and epoxy resin, thereby making the interface bonding between graphene and epoxy resin weak. Summary of the invention
[0006] In order to solve one or more of the above problems, the present invention discloses a method for preparing an epoxy resin composite material with low-temperature medium leakage resistance, which successfully coats the surface of MXene with an organic polymer through a chemical reaction, significantly improving the dispersibility of MXene in epoxy resin, and effectively solving the problem of poor compatibility between MXene and epoxy resin. PU-MXene can significantly improve the low-temperature medium leakage resistance of epoxy resin and improve the mechanical properties at the same time. Therefore, the resin matrix is very suitable for manufacturing composite cryogenic propellant tanks for launch vehicles.
[0007] The first object of the present invention is to provide a method for preparing an epoxy resin composite material having low-temperature medium leakage resistance, comprising the following steps:
[0008] Step 1. Mix LiF and HCl, add Ti3AlC2, and etch at 35-40°C for 24-48 hours; after the reaction is completed, centrifuge and wash until the pH of the supernatant is neutral to obtain a precipitate. Re-disperse the precipitate in deionized water, perform ultrasonication, and centrifuge, obtain the supernatant, and freeze-dry to obtain product A;
[0009] Step 2. Disperse product A evenly in Tris-HCl, add tannic acid and react at 20-30°C for 12-24h, centrifuge and freeze-dry to obtain product B;
[0010] Step 3. Disperse product B evenly in N,N-dimethylformamide, add toluene diisocyanate and react at 40-60°C for 10-30 min, centrifuge and freeze-dry to obtain PU-MXene;
[0011] Step 4. Disperse PU-MXene in acetone to obtain PU-MXene / acetone dispersion, add the PU-MXene / acetone dispersion into liquid epoxy resin, the mass of PU-MXene is 1.8-3.5wt% of the mass of epoxy resin, stir evenly by ultrasonication, remove acetone in a vacuum oven; add 20-30wt% of curing agent by mass of epoxy resin, dissolve it evenly at 60°C, and obtain PU-MXene / epoxy resin;
[0012] Step 5. Use vacuum-assisted resin transfer molding process to prepare epoxy resin / carbon fiber composite material with a thickness of 1 mm, place 6 layers of carbon fiber fabric on the heating table, place glass layers and distribution mesh on the carbon fiber fabric respectively, and then use PU-MXene / epoxy resin vacuum-assisted impregnation of carbon fiber, and cure it according to the step curing temperature of 130℃~160℃ / 2h and 150℃~180℃ / 2h to obtain PU-MXene epoxy resin / carbon fiber composite material.
[0013] In one embodiment, in step 1, the concentration of HCl is 9M, the mass ratio of Ti3AlC2, LiF and HCl is 1:1:20 to 1:1.5:25, the ultrasonic time is 30 to 60 min, and the centrifugal speed is 3500 to 5000 rpm, in order to obtain MXene sheets of different sizes.
[0014] In one embodiment, in step 2, the concentration of Tris-HCl is 0.01 M, the pH is 8.5, and the mass ratio of product A, tannic acid and Tris-HCl is 1:1:10000 to 1:2:15000, in order to obtain polytannic acid-modified MXene.
[0015] In one embodiment, in step 3, the mass ratio of product B, toluene diisocyanate and N,N-dimethylformamide is 1:1:5000 to 1:2:10000, in order to obtain PU-MXene coated with an organic polymer.
[0016] In one embodiment, in step 4, the concentration of the PU-MXene / acetone dispersion is 2 to 4 mg / mL.
[0017] In one embodiment, the curing agent in step 4 is 4,4'-diaminodiphenylmethane (DDM).
[0018] The second object of the present invention is to provide an epoxy resin / carbon fiber composite material prepared by the above method.
[0019] The third object of the present invention is to provide an application of an epoxy resin composite material in the preparation of aerospace propellant tanks.
[0020] Advantages and effects of the present invention:
[0021] (1) The present invention combines MXene and epoxy resin well, significantly improving the epoxy resin's resistance to low-temperature medium leakage while improving its mechanical properties. The prepared PU-MXene epoxy resin / carbon fiber composite material has good low-temperature anti-leakage performance and mechanical properties, and can be used in aerospace propellant tanks. The preparation method is simple and easy.
[0022] (2) The present invention successfully coated the organic polymer on the surface of MXene to prepare PU-MXene, and the use of PU-MXene in combination with epoxy resin improved the dispersibility of MXene in the epoxy resin, effectively solving the problem of poor compatibility between MXene and epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 TEM image of MXene in Example 1;
[0024] Figure 2 This is a transmission electron microscopy image of PU-MXene in Example 1;
[0025] Figure 3 This is a diagram of the 3wt% PU-MXene / epoxy resin tensile test specimen in Example 1;
[0026] Figure 4 This is a picture of the epoxy resin tensile test specimen in comparative example 1;
[0027] Figure 5 This is a low-temperature leakage test sample of 3wt% PU-MXene / epoxy resin carbon fiber composite material in Example 1;
[0028] Figure 6 This is a diagram of the low-temperature leakage performance testing equipment. DETAILED DESCRIPTION
[0029] Glossary:
[0030] MXene is a new type of two-dimensional material composed of layered transition metal carbides (TMC). MXene materials have many excellent properties and application potentials, including high conductivity, good mechanical properties, excellent electrochemical properties, high specific surface area, etc. The name of MXene materials comes from their structure. M represents transition metal, X represents elements such as carbon or ammonia, and ene represents the structural unit of graphene.
[0031] Materials used in the embodiments:
[0032] Epoxy resin: purchased from Nantong Xingchen Synthetic Materials Co., Ltd., brand 830 resin, epoxy value 0.52 mol;
[0033] The materials involved in the other embodiments can be obtained from commercial channels.
[0034] Embodiment 1:
[0035] This embodiment provides an epoxy resin composite material with low-temperature medium leakage resistance, which is prepared by the following method:
[0036] First, PU-MXene is prepared, including the following steps:
[0037] Step 1. After mixing LiF and HCl, add Ti3AlC2, the concentration of HCl is 9M, the mass ratio of Ti3AlC2, LiF and HCl is 1:1:20, and etch at 40°C for 24h; after the reaction is completed, centrifuge and wash the solution to pH 7, redisperse it in deionized water, sonicate it, and then centrifuge it for 1h at a centrifugal speed of 3500rpm, obtain the supernatant and freeze-dry it to obtain product A;
[0038] Step 2. Disperse product A evenly in Tris-HCl with a concentration of 0.01 M and a pH of 8.5. Add tannic acid and react at 25°C for 12 hours. The mass ratio of product A, tannic acid and Tris-HCl is 1:1:10000. Centrifuge the reaction solution to obtain a solid, which is then freeze-dried to obtain product B.
[0039] Step 3. Disperse product B evenly in N,N-dimethylformamide, add toluene diisocyanate and react at 60°C for 30 minutes. The mass ratio of product B, toluene diisocyanate and N,N-dimethylformamide is 1:1:5000. Centrifuge the reaction solution to obtain a solid and then freeze-dry it to obtain PU-MXene.
[0040] Preparation of PU-MXene / epoxy resin carbon fiber composites:
[0041] Step 5. Disperse PU-MXene in acetone to obtain 3 mg / mL PU-MXene / acetone dispersion, add the PU-MXene / acetone dispersion to liquid epoxy resin, the mass of PU-MXene is 3.0wt% of the mass of epoxy resin, and stir evenly at 200W ultrasonic power, 500r / min, and 30°C; bake in a vacuum oven at 60°C for 12h, remove excess acetone, weigh the mass of the solution in the oven, and the error between the mass of the solution and the sum of the masses of PU-MXene and epoxy resin shall not exceed 0.5%; then add 4,4`-diaminodiphenylmethane (DDM) curing agent (15wt% of the mass of epoxy resin) and dissolve it evenly at 60°C to obtain a 3.0wt% PU-MXene / epoxy resin solution.
[0042] Step 6. Prepare epoxy resin / carbon fiber composite material with a thickness of 1 mm by vacuum-assisted resin transfer molding process. Place 6 layers of carbon fiber fabric on a heating table, place a glass layer and a distribution mesh on the carbon fiber fabric, and then vacuum-assisted impregnate the carbon fiber with 3.0wt% PU-MXene / epoxy resin solution, and cure it at a step curing temperature of 130℃2h and 160℃2h to obtain a PU-MXene / epoxy resin carbon fiber composite material.
[0043] Among them, product A is MXene material, and its transmission electron microscope image is as follows Figure 1 As shown, the transmission electron microscopy image of PU-MXene is as follows Figure 2 shown.
[0044] Figure 3 This is a picture of the tensile specimen made of the PU-MXene / epoxy resin carbon fiber composite material prepared in this example.
[0045] Embodiment 2:
[0046] Different from Example 1, 3.5 wt% PU-MXene was added to the epoxy resin when preparing the carbon fiber composite material. The mechanical properties and anti-permeability properties were tested.
[0047] Embodiment 3:
[0048] A PU-MXene / epoxy resin carbon fiber composite material was prepared according to the method of Example 1. Different from Example 1, when preparing the PU-MXene / epoxy resin carbon fiber composite material, the addition amount of PU-MXene was 1.8 wt%.
[0049] Comparative Example 1:
[0050] Different from Example 1, when preparing the carbon fiber composite material, PU-MXene was not added to the epoxy resin, and the tensile specimen prepared was as follows: Figure 4 shown.
[0051] Comparative Example 2:
[0052] Different from Example 1, MXene without polymer coating was added, and 3.0 wt% MXene was mixed with epoxy resin.
[0053] Comparative Example 3:
[0054] A PU-MXene / epoxy resin carbon fiber composite material was prepared according to the method of Example 1. Different from Example 1, when preparing the PU-MXene / epoxy resin carbon fiber composite material, the addition amount of PU-MXene was 0.5wt%.
[0055] Comparative Example 4:
[0056] A PU-MXene / epoxy resin carbon fiber composite material was prepared according to the method of Example 1. Different from Example 1, when preparing the PU-MXene / epoxy resin carbon fiber composite material, the addition amount of PU-MXene was 4.0 wt%.
[0057] The properties of the epoxy resin composite materials of Examples 1 to 3 and Comparative Examples 1 to 4 were tested, wherein the tensile strength mechanical properties were measured at room temperature according to ASTM D638-22. The low temperature anti-leakage performance was measured according to the national standard GB / T 1038-2000, and the test results are shown in Table 1. Figure 5 A low-temperature leakage test specimen made of the PU-MXene / epoxy resin carbon fiber composite material prepared in Example 1. Figure 6 It is a low temperature leakage performance test equipment.
[0058] Table 1: Performance test results of epoxy resin composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3
[0059]
[0060] The low temperature leakage performance of the samples of Examples 1 to 3 and Comparative Examples 1 to 4 was tested. The leakage value of the pure epoxy resin / carbon fiber composite material prepared in Comparative Example 1 was 6.5×10 -4 Pa·m 3 / s, which cannot meet the requirements of the aviation field for the low-temperature leakage performance of composite materials (less than 5×10 -5 Pa·m 3 / s); with the increase of PU-MXene content, the leakage value of epoxy resin / carbon fiber composite material also decreases, which is 1.2×10 -5 Pa·m 3 / s(0.5wt%PU-MXene),9.2×10 -6 Pa·m 3 / s(1.8wt%PU-MXene), 2.4×10 -6 Pa·m 3 / s (3.0wt% PU-MXene). When the addition amount of PU-MXene is 3.5wt%, the leakage value is 3.2×10 -7 , which meets the requirements of the aviation field for low-temperature leakage performance of composite materials, indicating that PU-MXene can effectively improve the anti-leakage performance of epoxy resin matrix. When the addition amount of PU-MXene reaches 4.0wt%, the leakage value is 9.6×10 -6 Pa·m 3 / s, the anti-leakage performance has decreased. The reason is that the excessive PU-MXene cannot be evenly dispersed in the epoxy resin, resulting in PU-MXene agglomeration, affecting its low-temperature leakage performance. In Control Example 2, organic-coated MXene was not used, and MXene could not be evenly dispersed in the epoxy resin, resulting in a decrease in anti-permeability. The tensile strengths of the samples in Examples 1 to 3 were 85, 79, and 82 MPa, respectively, and the tensile strengths of the samples in Control Examples 1 to 4 were 75, 55, 79, and 70 MPa, respectively. In summary, when the addition amount of PU-MXene is 3.5wt%, good low-temperature anti-permeability and mechanical properties are guaranteed. When the addition amount of PU-MXene exceeds 3.5wt%, the performance is all reduced.
Claims
1. A method for preparing an epoxy resin composite material having low-temperature medium leakage resistance, characterized in that: include: Step 1. Ti3AlC2 is etched by LiF and HCl. After the reaction is completed, the supernatant is centrifuged and washed until the pH value is neutral to obtain a precipitate. The precipitate is redispersed in water and then ultrasonicated and centrifuged again. The supernatant is obtained and freeze-dried to obtain product A. Step 2. Disperse product A evenly in Tris-HCl solution, add tannic acid, react, centrifuge, and freeze-dry to obtain product B; Step 3. Disperse product B evenly in N,N-dimethylformamide, add toluene diisocyanate, react, centrifuge, and freeze-dry to obtain PU-MXene; Step 4. Disperse PU-MXene in acetone to obtain a PU-MXene / acetone dispersion, add the PU-MXene / acetone dispersion to liquid epoxy resin, stir evenly with ultrasonic wave, remove acetone, add curing agent, dissolve, and obtain a PU-MXene / epoxy resin solution; Step 5. The epoxy resin / carbon fiber composite material is prepared by a vacuum-assisted resin transfer molding process, the carbon fiber fabric is heated, a glass layer and a distribution mesh are placed on the carbon fiber fabric, and then the carbon fiber fabric is vacuum-assisted impregnated with a PU-MXene / epoxy resin solution and cured to obtain an epoxy resin / carbon fiber composite material.
2. The method according to claim 1, characterized in that: In step 4, the mass of PU-MXene in the PU-MXene / epoxy resin solution is 1.8 to 3.5 wt % of the mass of the epoxy resin.
3. The method according to claim 1, characterized in that In the step 1, the mass ratio of Ti3AlC2, LiF and HCl is 1:1:20 to 1:1.5:
25.
4. The method according to claim 1, characterized in that: In the step 1, the etching parameters of Ti3AlC2 etching by LiF and HCl are: etching at 35-40°C for 24-48h.
5. The method according to claim 1, characterized in that In step 2, the concentration of Tris-HCl is 0.01 M and the pH is 8.
5.
6. The method according to claim 1, characterized in that In the step 2, the mass ratio of product A, tannic acid and Tris-HCl is 1:1:10000 to 1:2:15000.
7. The method according to claim 1, characterized in that In the step 3, the mass ratio of product B, toluene diisocyanate and N,N-dimethylformamide is 1:1:5000-1:2:10000, the reaction temperature is 50-70°C, and the reaction time is 20-40 minutes.
8. The method according to claim 1, characterized in that The curing in step 5 is performed at a step curing temperature of 130° C. to 160° C. / 2 h and 150° C. to 180° C. / 2 h.
9. An epoxy resin composite material, characterized in that: The epoxy resin composite material is prepared by a method according to any one of claims 1 to 8.
10. Use of the epoxy resin composite material according to claim 9 in preparing aerospace propellant tanks.
Citation Information
Patent Citations
A method for preparing epoxy resin / graphite microflake composite materials for aerospace applications
CN103435975B
Preparation method of epoxy resin / MXene composite material
CN109880290A
Self-repairing MXene / polyurethane thermoelectric composite material and preparation method thereof
CN110713706A